2020
DOI: 10.1002/eji.202048753
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of HLA class II binding to the LAG‐3 T cell co‐inhibitory receptor

Abstract: Immune checkpoint inhibitors (antibodies that block the T cell co-inhibitory receptors PD-1/PD-L1 or CTLA-4) have revolutionized the treatment of some forms of cancer. Importantly, combination approaches using drugs that target both pathways have been shown to boost the efficacy of such treatments. Subsequently, several other T cell inhibitory receptors have been identified for the development of novel immune checkpoint inhibitors. Included in this list is the co-inhibitory receptor lymphocyte activation gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…demonstrated that strong affinity of antigenic peptide for MHCII and expression of MHCII accessory molecules substantially increase LAG3 binding to MHCII. As the authors note, this indicates that LAG3 function is dependent on APC properties, the presented peptides and MHC haplotypes, bestowing a target selectivity that is unique among immune checkpoints ( 35 , 40 ).…”
Section: Ligand Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that strong affinity of antigenic peptide for MHCII and expression of MHCII accessory molecules substantially increase LAG3 binding to MHCII. As the authors note, this indicates that LAG3 function is dependent on APC properties, the presented peptides and MHC haplotypes, bestowing a target selectivity that is unique among immune checkpoints ( 35 , 40 ).…”
Section: Ligand Bindingmentioning
confidence: 99%
“…Some have suggested that LAG3 inhibitory function is a result of competitive inhibition of CD4 due to its shared evolutionary origin and the fact that it binds MHCII with far greater affinity ( 35 , 39 , 40 , 46 ). However, no evidence suggests LAG3 inhibits CD4-ligand interaction during T cell activation.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Some studies suggested that pHLA-II is a LAG3 receptor ( 50 52 ), and recently, Maclachlan et al. showed that LAG3 can directly and competitively bind with pHLA-IIto influence the bind of CD4 with pHLA-II, further inhibiting T cell activation ( 53 ).…”
Section: The Biological Effect Of Lag3/fgl1 On Different Tumorsmentioning
confidence: 99%
“…From above all, the discrepancy of LAG3 exerts positively or negatively in immune functions can be attributed to the complexity of tumor immune microenvironment and tumor heterogeneity, besides, LAG3 may not create immunosuppression when acting alone, but only when acting in combination with other immune checkpoints such as PD1. Some studies suggested that pHLA-II is a LAG3 receptor (50-52), and recently, Maclachlan et al showed that LAG3 can directly and competitively bind with pHLA-IIto influence the bind of CD4 with pHLA-II, further inhibiting T cell activation (53).…”
Section: The Biological Effect Of Lag3/fgl1 On Different Tumors Immun...mentioning
confidence: 99%
“…Consequently, our lab has recently used surface plasmon resonance (SPR) (see Technical box ) to directly measure binding between HLA-DR1 and LAG-3:Fc. Using titrated amounts of immobilised proteins on the sensor chip, we estimated the monovalent interaction between HLA-DR1 bearing a high-affinity peptide (Influenza A Haemagglutinin 306–318 ) and LAG-3 to be in the low micromolar range (K D ≈ 13 µM) [ 35 ]. This affinity measurement is in a similar range as HLA-I binding co-inhibitory receptors, such as the ILT/LILRB family [ 36 ] but still significantly stronger affinity than that of HLA-II/CD4 which is estimated at K D = 2.5 mM [ 37 ].…”
Section: Lag-3 Ligands: Not Just Mhc-ii?mentioning
confidence: 99%